THE RESULTS OF STUDYING THE MORPHOLOGY AND BIOLOGY OF THE CAUSATIVE AGENT OF PARAMPHISTOMATOUS DISEASE IN CATTLE - Taylaqov Tolip; Bazarbayeva Aynura; Allambergenov Davletbay (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the results of studying the morphology and biology of causative agents of paramphistomatous disease in cattle.